Feasibility of Booklet on the Utilization of Plants as Food Additives by the Montasik Community as a Reference for the Nutrition and Health Course - Eriawati Eri; Nurdin Amin; Nafisah Hanim; Ita Kausari (Jurnal Pengembangan Profesi Guru dan Dosen, 2025)
Food additives are substances intentionally added to food to influence its properties and characteristics. These additives include food colorings and flavorings. Natural colorings are derived from plants that have the potential to produce color. The Nutrition and Health course discusses food sources and nutrients (nutritional substances) and their functions for health. The obstacle faced by students in the Nutrition and Health course is related to learning about the use of plants as food additives, specifically the need for additional reference material on natural additives. This research aims to analyze the feasibility test results of a booklet based on the research "Utilization of Plants as Food Additives by the Montasik Community" as a reference for the Nutrition and Health course. The approach used in this research is qualitative. The sampling method used is Purposive Sampling, which is sampling based on specific considerations. This research was conducted in the Faculty of Education and Teacher Training in March 2025. Data collection was carried out through validation questionnaires. Data were analyzed using percentage formulas. The validation by material experts resulted in a percentage of 84.7%, categorized as feasible for use, and the validation by media experts resulted in a percentage of 80%, also categorized as feasible for use. The average score obtained was 82.35%, indicating that the Booklet is Very Feasible for use